Searching for a new Kenya politics and social media on the streets of Mombasa - Diepeveen, Stephanie 1986- (Cambridge University Press, 2021)
"Just around the corner from the noise and congestion of the central bus terminal in Mombasa, there is a maze of narrow streets where shoe polishers, cobblers and other small-scale tradesmen set up stands. Amidst these streets, there is a corner where three roads converge and create a clearing large enough to accommodate a bigger gathering. Anywhere from 10 to more than 100 people, mostly men, gather at this corner, a few sitting on makeshift wooden benches, but most standing"--
Keywords: Zivilgesellschaft; Politische Beteiligung; Social Media; Kenia; Kenya / Politics and government; Social media / Kenya / Mombasa; Kenya / Economic conditions; Economic history; Politics and government; Social media; Kenya; Kenya / Mombasa